2020
DOI: 10.7899/jce-19-12
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive analysis of clinical application of patient-reported outcome measures and screening tools for low back pain patients in US chiropractic teaching institutions

Abstract: Objective To describe the clinical use of patient-reported outcome measures (PROMs) and screening tools (STs) for low back pain (LBP) in clinics of chiropractic teaching institutions in the United States. Methods A descriptive analysis was completed with data collection achieved between June 2018 and March 2019. PROMs/STs were classified as disability/functional measures, pain measures, psychosocial measures, and other measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Patients averaged 7 chiropractic visits during their episode of care, with 83% having 11 visits or less. While 95% of chiropractic teaching institutions report the routine use of PROMs for low back pain patients [ 28 ], evidence about the current use of PROMs among chiropractors in routine clinical practices is limited [ 14 ]. One study reported that almost 30% of a chiropractor population in Australia don't routinely assess PROMs in clinical practice for low back pain patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients averaged 7 chiropractic visits during their episode of care, with 83% having 11 visits or less. While 95% of chiropractic teaching institutions report the routine use of PROMs for low back pain patients [ 28 ], evidence about the current use of PROMs among chiropractors in routine clinical practices is limited [ 14 ]. One study reported that almost 30% of a chiropractor population in Australia don't routinely assess PROMs in clinical practice for low back pain patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Patients averaged 7 chiropractic visits during their episode of care, with 83% having 11 visits or less. While 95% of chiropractic teaching institutions report the routine use of PROMs for low back pain patients, 22 evidence about the current use of PROMs among chiropractors in routine clinical practices is limited. 12 One study reported that almost 30% of a chiropractor population in Australia don't routinely assess patient-reported outcomes in clinical practice for low back pain patients.…”
Section: Discussionmentioning
confidence: 99%